Changes in souring development, nutritional and functional properties during fermentation of cowpea-fortified nixtamalized maize - Afoakwa, E.O.; Aidoo, P.R. (Handbook of Environmental Chemistry, Volume 5: Water Pollution, 2006)
Spontaneous fermentation of maize produces lactic acids resulting in souring or acidification with associated improvement in taste, flavour and texture of the derived products. When combined with nixtamalization and cowpea fortification, it is expected to improve the nutritional quality and product functionality of maize based foods and as well introduce variety to maize processing. This study was carried out to investigate the changes in souring development, nutritional quality and functional properties during spontaneous fermentation of cowpea-fortified nixtamalized maize. A 2 x 3 x 3 factorial experimental design, with fermentation medium (water, coconut water), fermentation time (0, 24, 48 hours) and cowpea level (0, 15, 30 %) was performed. Nixtamalized maize was prepared by boiling whole maize in 1 % lime solution for 30 minutes, steeped in excess lime, milled into meal and kneaded into a dough using water or coconut water. The blends were fermented for the specific times and analysed for pH, titratable acidity, water absorption capacity, colour, protein and ash. The presence of lime and cowpea influenced the pH, titratable acidity, water absorption, colour, protein and ash content of the fermented cowpea-fortified maize. Addition of cowpea increased most of the studied indices whiles pH of all the blends decreased (6.15-4.45) with a corresponding increase in titratable acidity (0.008-0.045 g/100g lactic acid) with increase in fermentation time. There was however no significant (p<0.05) difference in the effect of fermentation medium on these indices suggesting that coconut water could be used as an alternative fermentation medium for maize dough fermentation without any effect in souring development. Fermentation and cowpea fortification can therefore be used to increase the nutritive value of nixtamalized maize with acceptable souring and product quality characteristics. Copyright ©2006 The Berkeley Electronic Press. All rights reserved.
Keywords: Coconut water; Cowpea fortification; Fermentation; Functional properties; Maize; Nixtamalization; Nutritive value; Souring development